The money market in France - WILSON, J.S.G. (PSL Quarterly Review, 2013)
This article examines recent changes in French money markets. The main market is the inter-bank money market in balances with the Bank of France and the operations of this market are outlined in some detail. The government bond market dominates the fixed interest markets as a whole; because the activities of these markets impinge on the money markets their operations are also surveyed. The French financial futures market, the Marche a Terme International de France (MATIF), is also covered along with details of the methods of influence used by the Bank of France over money markets. JEL: E41, E58